The relativity of authenticity: Notions of authenticity in the Cape Winelands cultural landscape and the impact of wine tourism on cultural heritage - Joubert, Elize (School of Architecture, Planning and Geomatics, 2016)
This study explores various notions of authenticity in tourism experience and seeks to establish if these notions are compatible with the concept of authenticity in conservation of the built environment. Three wine farms in the Cape Winelands cultural landscape, a proposed serial World Heritage Site, have been studied. The study suggests that object-related or material authenticity is being replaced with alternative notions of authenticity in tourism and that the toured object, for the purpose of winelands tourism in the Western Cape during this period, no longer needs to be authentic.